2015
DOI: 10.1016/j.scitotenv.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Origins and processes of groundwater salinization in the urban coastal aquifers of Recife (Pernambuco, Brazil): A multi-isotope approach

Abstract: In the coastal multilayer aquifer system of a highly urbanized southern city (Recife, Brazil), where groundwaters are affected by salinization, a multi-isotope approach (Sr, B, O, H) was used to investigate the sources and processes of salinization. The high diversity of the geological bodies, built since the Atlantic opening during the Cretaceous, highly constrains the heterogeneity of the groundwater chemistry, e.g. Sr isotope ratios, and needs to be integrated to explain the salinization processes and groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 73 publications
1
51
0
10
Order By: Relevance
“…While likely to be much more localised in time and space than VMGRs, due to the current sea level position being relatively high by recent geological standards, there are examples of low lying areas where inundation by seawater in previous times (e.g. the mid-Holocene) appears evident (Giambastiani et al, 2012;Vaeret et al, 2012;Currell et al, 2014;Cary et al, 2015). Key controls on the presence of such trapped marine water in coastal aquifers are changes in relative coastline elevation due to sea level change, evolution of the aquifer water balance, and the geological structure and aquifer properties, which control the rate of re-equilibration of the interface following a sea level change (Kooi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…While likely to be much more localised in time and space than VMGRs, due to the current sea level position being relatively high by recent geological standards, there are examples of low lying areas where inundation by seawater in previous times (e.g. the mid-Holocene) appears evident (Giambastiani et al, 2012;Vaeret et al, 2012;Currell et al, 2014;Cary et al, 2015). Key controls on the presence of such trapped marine water in coastal aquifers are changes in relative coastline elevation due to sea level change, evolution of the aquifer water balance, and the geological structure and aquifer properties, which control the rate of re-equilibration of the interface following a sea level change (Kooi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To address the possibility of seawater intrusion in Naozhou island, we referred to the hydrochemistry data of Naozhou island investigated by Zhang et al [34] in March 2011 (Table 5). These hydrochemical data showed that the confined groundwater in the southern and eastern coastal area (e.g., samples 26,22,20, and 14 in Figure 1(d)) has been saline with TDS value of 1.39-10.28 g/L. This means that freshwater-seawater mixing zones in the confined aquifers of Naozhou island have extended landward.…”
Section: Salinity Indications Of the Seawater Intrusion Riskmentioning
confidence: 89%
“…The application of chemistry and hydrogen-oxygen isotopes can be used also to identify processes of groundwater salinization induced by seawater intrusion [21][22][23][24][25]. In addition, many 2 Geofluids other isotopes (e.g., radium, carbon, chlorine, boron, and strontium) have been used as tracers for characterizing the hydrogeological conditions and hydrochemical processes in coastal aquifers, specifically identifying submarine groundwater discharge and describing seawater intrusion [10,13,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Overexploitation of groundwater can therefore result in seawater intrusion, as well as related environmental issues such as land subsidence. Seawater intrusion has become a global issue and related studies can be found from coastal aquifers around the world, including Israel (Sivan et al, 2005;Yechieli et al, 2009;Mazi et al, 2014), Spain (Price and Herman, 1991;Pulido-Leboeuf, 2004;Garing et al, 2013), France (Barbecot et al, 2000;de Montety et al, 2008), Italy (Giambastiani et al, 2007;Ghiglieri et al, 2012), Morocco (Bouchaou et al, 2008;El Yaouti et al, 2009), the USA (Gingerich and Voss, 2002;Masterson, 2004;Langevin et al, 2010), Australia (Zhang et al, 2004;Narayan et al, 2007;Werner, 2010), China (Xue et al, 2000;Han et al, 2011Han et al, , 2015, Vietnam , Indonesia (Rahmawati et al, 2013), India (Radhakrishna, 2001;Bobba, 2002) and Brazil (Montenegro et al, 2006;Cary et al, 2015). Werner et al (2013) provides a comprehensive review of seawater intrusion processes, investigation and management.…”
mentioning
confidence: 99%
“…Relatively few studies have focused on delineating complex interactions among the surface-groundseawater continuum in estuarine environments, including the effects of vertical infiltration of seawater into aquifers through river channels, compared to subsurface lateral landward migration of the freshwater-saltwater interface. Recent data indicate that such processes may be more important in causing historical salinization of coastal groundwater than previously appreciated (e.g., Cary et al, 2015;Lee et al, 2016;Larsen et al, 2017).…”
mentioning
confidence: 99%